MODEL PEMBELAJARAN BERBASIS PONDOK PESANTREN DALAM MEMBENTUK KARAKTER SISWA - Hasan, Muhammad Nur (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
The study aimed at gaining a deep understanding and finding out the implementation of character based learning model atRoudhotut Tholibin Islamic Boarding School, Rembang, Central Java.This study was considered as qualitative research. It was commonly conducted in natural settings where the researcher paid muchattention to the social context. Method of data collection was conducted to gather the responses and any information about thebehaviors from the participants. Qualitative approach was employed to analyze the data relying on the results of the interviewand the secondary data from the original sources as well. The numeric data were employed in purpose of avoiding a subjectiveperspective derived from the analysis of the results of the interview.According to the results, this study concluded that some efforts and plans had been carried out to build the students’ character.Furthermore, the school rules were clearly stated in the rule book presenting about preparing the classroom duties, askingpermission, breaking the rules and the consequences. The teachers also guided the students in mastering Qur’an reading,writing, and memorization as well.The study aimed at gaining a deep understanding and finding out the implementation of character based learning model atRoudhotut Tholibin Islamic Boarding School, Rembang, Central Java.This study was considered as qualitative research. It was commonly conducted in natural settings where the researcher paid muchattention to the social context. Method of data collection was conducted to gather the responses and any information about thebehaviors from the participants. Qualitative approach was employed to analyze the data relying on the results of the interviewand the secondary data from the original sources as well. The numeric data were employed in purpose of avoiding a subjectiveperspective derived from the analysis of the results of the interview.According to the results, this study concluded that some efforts and plans had been carried out to build the students’ character.Furthermore, the school rules were clearly stated in the rule book presenting about preparing the classroom duties, askingpermission, breaking the rules and the consequences. The teachers also guided the students in mastering Qur’an reading,writing, and memorization as well.